Growth in renal failure: a longitudinal study of emotional and behavioural changes during trials of growth hormone treatment. Issue 3 (1st March 1998) - Postlethwaite, R J; Eminson, D M; Reynolds, J M; Wood, A J; Hollis, S
Abstract : Growth and psychological functioning were studied in 30 patients with renal failure over a two year period following the offer of growth hormone treatment for significant short stature. Parents' concerns about growth decreased significantly during the study. Twenty eight parents (93%) accepted growth hormone treatment; most (74%) were satisfied with it and would opt for it again (89%). The views of these parents were unrelated to growth outcome in their child. This suggests that the positive responses were related more to the effort to improve growth than to any objective treatment success. In contrast children's reduction in concern about growth, satisfaction with treatment (36%), and decision to opt for growth hormone again (50%) were all significantly related to improvement in growth. Parents' reports of non-compliance increased significantly from 41% at 1 year to 91% at 2 years in the group as a whole. No significant changes were identified in maternal mental distress and no additional costs to the psychological health of the children seem to have resulted from the introduction of growth hormone treatment. A group of children was identified who accepted treatment but had continued poor growth. These appeared to be at particular risk of both physical problems and associated or consequent psychological difficulties.